Sorafenib plus valproic acid for infant spinal glioblastoma - Rokes, Christopher Alan; Remke, Mark; Guha-Thakurta, Nandita; Witt, Olaf; Korshunov, Andrey; Pfister, Stephan; Wolff, Johannes E. (Journal of pediatric hematology - oncology, 2010)
Spinal glioblastoma multiforme (GBM) is rare in children. New therapeutic options should be explored given the poor outcomes reported. We describe the case of an infant with spinal GBM whose condition worsened despite radiotherapy and chemotherapy. Immunohistochemical analysis of the tumor sample showed activation of the Raf-MEK-ERK pathway. Targeted pharmacologic therapy with sorafenib plus valproic acid led to decrease in the size of the tumor and improvement of symptoms. We conclude that regulation of the mitogen-activated protein kinase pathway using sorafenib plus valproic acid warrants further investigation for the management of childhood GBM.